Intestinal toxicity of the new type A trichothecenes, NX and 3ANX. (February 2022) - Pierron, Alix; Neves, Manon; Puel, Sylvie; Lippi, Yannick; Soler, Laura; Miller, J. David; Oswald, Isabelle P.
Abstract: NX and its acetylated form 3ANX are two new type A trichothecenes produced by Fusarium graminearum whose toxicity is poorly documented . The aim of this study was to obtain a general view of the intestinal toxicity of these toxins. Deoxynivalenol (DON), which differs from NX by the keto group at C8, served as a benchmark. The viability of human intestinal Caco-2 cells decreased after 24 h of exposure to 3 μM NX (−21.4%), 3 μM DON (−20.2%) or 10 μM 3ANX (−17.4%). Histological observations of porcine jejunal explants exposed for 4 h to 10 μM of the different toxins showed interstitial edema and cellular debris. Explants exposed to NX also displayed cell vacuolization, a broken epithelial barrier and high loss of villi. Whole transcriptome profiling revealed that NX, DON and 3ANX modulated 369, 146 and 55 genes, respectively. Functional analyses indicated that the three toxins regulate the same gene networks and signaling pathways mainly; cell proliferation, differentiation, apoptosis and growth, and particularly immune and pro-inflammatory responses. Greater transcriptional impacts were observed with NX than with DON. In conclusion, our data revealed that the three toxins have similar impacts on the intestine but of different magnitude: NX > DON ≫ 3ANX. NX and 3ANX should consequently be included in overall risk analysis linked to the presence of trichothecenes in our diet. Graphical abstract: Image 1 Highlights: Differential cytotoxicity in human Caco-2 cells: NX = DON>3ANX. Number of differentially expressed genes in intestinal explant NX ≫ DON>3ANX. NX, 3ANX and DON modulate pathways mainly related to inflammation and immune response.